Between Procreation and Poverty Alleviation: Re-evaluating Shafi'i Jurisprudence on State-Mandated Vasectomy - Imam Thobroni; Suliyanto (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
This study aims to examine the legality of vasectomy as a prerequisite for receiving social assistance from the perspective of Shafi’i jurisprudence. The emergence of vasectomy requirements in welfare policies has generated debate in Muslim societies because it intersects with issues of reproductive rights, bodily autonomy, and religious ethics. Such policies raise questions about whether state efforts to control population growth and poverty align with the principles and objectives of Islamic law. This research employs a qualitative, normative approach, drawing on library research methods. Classical and contemporary Shafi’i jurisprudential texts are analysed through the framework of maqaṣid al-Shari’ah and Islamic legal maxims. The findings show that vasectomy is generally categorized as impermissible because it permanently eliminates reproductive capacity and contradicts the principle of ḥifẓ al-naṣl. Economic hardship and administrative interests cannot be classified as darurah that would justify permanent sterilization. Conditioning social assistance on vasectomy potentially creates structural coercion for economically vulnerable communities. This policy may therefore produce tensions between welfare objectives and Islamic legal principles. This study contributes to the discourse on Islamic public policy and recommends interdisciplinary research integrating fiqh, socio-legal analysis, and public policy studies.